The Effect of Lift The Flap Book About Fat-Soluble Vitamins on Knowledge and Attitude of School-Age Children 10-12 Years - Harvianto, Audrey Zalika; Melani, Vitria; Sitoayu, Laras; Harna, Harna (Media Gizi Indonesia, 2022)
School-age children are one of the at risk groups for fat-soluble vitamin deficiencies. The consequence that could be experienced is the unoptimal growth of bones and teeth. In addition, it can affect the child's growth and development. One of the things that can cause this condition is a child's lack of knowledge about fat-soluble vitamins. The efforts that can be made to increase knowledge about fat-soluble vitamins is by using interactive media such as Lift The Flap Book as a learning medium. The purpose of this research was to the measure the influence of Lift The Flap Book on the knowledge and attitudes of school-age children about the importance of fat-soluble vitamins in food. This research was a quasi-experimental study with a sample of 33 children aged 10-12 years with a one group pre-test and post-test design. The results of this study are the average knowledge score of fat-soluble vitamins with media interventions Lift The Flap Book during the pre-test, post-test 1, and post-test 2 was 62.00; 81.99; and 78.14. Then, the attitude of fat-soluble vitamins was 64.83; 77.4; and 76.95. This result showed that the Lift The Flap Book media can increase the knowledge and attitudes about fat-soluble vitamins (p=0.000) among school-age children 10-12 years.